When Ads Meet Fascism On YouTube: What The Recent Google-Scandal Tells Us About Big Data Capitalism (Long version) - Fuchs, Christian (Medium.com)

When Ads Meet Fascism On YouTube: What The Recent Google-Scandal Tells Us About Big Data Capitalism (Short version) - Fuchs, Christian (Huffington Post)

Generation and active manipulation of qubits in LiNbO3-based integrated circuits - Meier, Torsten; Sharapova, P.R.; Luo, K.H.; Herrmann, H.; Reichelt, Matthias; Silberhorn, C. (arXiv preprint arXiv:1704.03769)

Hacia un estudio Marxiano del Internet. Translated by Adrián Montero Morera - Fuchs, Christian (Revista de Ciencias Sociales Universidad de la Universidad de Costa Rica)

Fake News Is Not Just The Word Of The Year, But A Danger To Democracy That Can Only Be Overcome By Adequate Legal And Media Reforms - Fuchs, Christian (Huffington Post)

What is to Be Done? The Role of the New and the Old in Media Theory – The Moment for Critical Digital and Social Media Studies - Fuchs, Christian (Westminster Papers in Communication and Culture)

Donald Trump: A Critical Theory-Perspective on Authoritarian Capitalism - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

How the Frankfurt School Helps Us to Understand Donald Trump’s Twitter Populism - Fuchs, Christian (The Huffington Post)

Towards the Public Service Internet as Alternative to the Commercial Internet - Fuchs, Christian (ORF Texte No. 20 – Öffentlich-Rechtliche Qualität im Diskurs)

Written Evidence Submitted to the House of Commons-Digital, Culture, Media and Sport Select Committee’s Inquiry on Fake News. Published on November 28, 2017 - Fuchs, Christian

Organic Polymers as Porogenic Structure Matrices for Mesoporous Alumina and Magnesia - Chen, Zimei; Weinberger, Christian; Tiemann, Michael; Kuckling, Dirk (Processes)
Dimethylacrylamide-based hydrogels were utilized as porogenic matrices in the synthesis of mesoporous aluminum oxide (γ-Al2O3) with specific BET surface areas up to 360 m2 g–1. Polymers with molecular mass in the range 12000–35000 g mol–1 were synthesized from dimethylacrylamide and various comonomers by free-radical polymerization. Photo-cross-linking of the polymers and impregnation with aluminum nitrate [Al(NO3)3] was carried out in a single step, followed by formation of Al(OH)3/AlO(OH) and subsequent calcination. Calcination led to the formation of mesoporous Al2O3 and simultaneous combustion of the hydrogel. The structural properties of the products were characterized by powder XRD, N2 physisorption analysis, Hg intrusion porosimetry, and thermogravimetric analysis.

Exkursinhalte in der fachmathematischen Lehramtsausbildung: Wie man das Wesen und die Rolle der Mathematik vermittelt. - Weich, Tobias; Hoffmann, Max (die hochschullehre)

A. Voß: Reisen erzählen. Erzählrhetorik, Intertextualität und Gebrauchsfunktionen des adligen Bildungsreiseberichts in der Frühen Neuzeit. Heidelberg 2016 - Moritz, Tilman (DIEGESIS)

An Army in Revolt? Military Disorder during the Reign of Commodus - Moritz, Tilman (Ancient World Magazine)

A Novel Target Separation Algorithm Applied to The Two-Dimensional Spectrum for FMCW Automotive Radar Systems - Fei, Tai; Grimm, Christopher; Farhoud, Ridha; Breddermann, Tobias; Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE International conference on microwave, communications, anthenas and electronic systems)
In this paper, we apply a high-resolution approach, i.e. the matrix pencil method (MPM), to the FMCW automotive radar system to separate the neighboring targets, which share similar parameters, i.e. range, relative speed and azimuth angle, and cause overlapping in the radar spectrum. In order to adapt the 1D model of MPM to the 2D range-velocity spectrum and simultaneously limit the computational cost, some preprocessing steps are proposed to construct a novel separation algorithm. Finally, this algorithm is evaluated in both simulation and real data, and the results indicate a promising performance.

Hypothesis Test for the Detection of Moving Targets in Automotive Radar - Grimm, Christopher; Breddermann, Tobias; Farhoud, Ridha; Fei, Tai; Warsitz, Ernst; Haeb-Umbach, Reinhold (IEEE International conference on microwave, communications, anthenas and electronic systems (COMCAS))
In this paper, we present a hypothesis test for the classification of moving targets in the sight of an automotive radar sensor. For this purpose, a statistical model of the relative velocity between a stationary target and the radar sensor has been developed. With respect to the statistical properties a confidence interval is calculated and targets with relative velocity lying outside this interval are classified as moving targets. Compared to existing algorithms our approach is able to give robust classification independent of the number of observed moving targets and is characterized by an instantaneous classification, a simple parameterization of the model and an automatic calculation of the discriminating threshold.

Hidden Markov Model Variational Autoencoder for Acoustic Unit Discovery - Ebbers, Janek; Heymann, Jahn; Drude, Lukas; Glarner, Thomas; Haeb-Umbach, Reinhold; Raj, Bhiksha (INTERSPEECH 2017, Stockholm, Schweden)
Variational Autoencoders (VAEs) have been shown to provide efficient neural-network-based approximate Bayesian inference for observation models for which exact inference is intractable. Its extension, the so-called Structured VAE (SVAE) allows inference in the presence of both discrete and continuous latent variables. Inspired by this extension, we developed a VAE with Hidden Markov Models (HMMs) as latent models. We applied the resulting HMM-VAE to the task of acoustic unit discovery in a zero resource scenario. Starting from an initial model based on variational inference in an HMM with Gaussian Mixture Model (GMM) emission probabilities, the accuracy of the acoustic unit discovery could be significantly improved by the HMM-VAE. In doing so we were able to demonstrate for an unsupervised learning task what is well-known in the supervised learning case: Neural networks provide superior modeling power compared to GMMs.

„I think this is going to be our place for the next days!“. Ein subjektabhängiger Tagungsbericht zu „Popular Music Studies Today – 19th Biennial Conference of the International Association for the Study of Popular Music“ (26.-30.06.2017). - Jacke, Christoph

Multi-Stage Coherence Drift Based Sampling Rate Synchronization for Acoustic Beamforming - Schmalenstroeer, Joerg; Heymann, Jahn; Drude, Lukas; Boeddeker, Christoph; Haeb-Umbach, Reinhold (IEEE 19th International Workshop on Multimedia Signal Processing (MMSP))
Multi-channel speech enhancement algorithms rely on a synchronous sampling of the microphone signals. This, however, cannot always be guaranteed, especially if the sensors are distributed in an environment. To avoid performance degradation the sampling rate offset needs to be estimated and compensated for. In this contribution we extend the recently proposed coherence drift based method in two important directions. First, the increasing phase shift in the short-time Fourier transform domain is estimated from the coherence drift in a Matched Filterlike fashion, where intermediate estimates are weighted by their instantaneous SNR. Second, an observed bias is removed by iterating between offset estimation and compensation by resampling a couple of times. The effectiveness of the proposed method is demonstrated by speech recognition results on the output of a beamformer with and without sampling rate offset compensation between the input channels. We compare MVDR and maximum-SNR beamformers in reverberant environments and further show that both benefit from a novel phase normalization, which we also propose in this contribution.

Pop im Kopp. Ein Vorschlag zur Image-Analyse eines schwer fassbaren Phänomens zwischen Fakt, Fiktion und Fake. - Jacke, Christoph; Westerbarkey, Joachim (Medien & Zeit. Kommunikation in Vergangenheit und Gegenwart.)